PENJADWALAN IMUNISASI ANAK BERBASIS SMS GATEWAY (Information Technology and Telematics, 2014)
Abstract - SMS gateway can be interpreted as a liaison to the SMS data traffic, whether sent or received. Diverse range of services, from simple information such as the type of service scheduling info. The advantage gained from the SMS Gateway is as a medium of communication message (SMS) that connects the computer to the phone via a modem connection. The service contains information about immunization schedules for children. For immunization scheduling itself is still using the manual way, so that the required application information system scheduling-based SMS Gateway now want to remind Parents immunization schedules will be his son. To solve the solution then the author makes application SMS Gateway. This information system aims to help Parents when considering his computerized immunization schedule as well as help the admin to note the immunization schedules of his patients. This information system development method using SDLC and to his programming language using PHP with a MySQL database as well as for directed using DFD (Data Flow diagrams) and ERD (Entity Relation Diagram). With this immunization scheduling information system, it is expected to address the problems of child immunization schedule will be forgotten. Keyword : Information System, scheduling of immunizations, PHP, MySQL